Earnings Management in the Manufacturing Industry in the Post-COVID-19 Era - Ramlah, Ramlah; Rizal, Muhammad; Sujatmiko, Sujatmiko; Lutfi, Andi (Jurnal Manajemen Bisnis, 2026)
This study aimed to evaluate the influence of deferred tax assets, deferred tax liabilities, and tax planning on earnings management from the perspective of government auditors. A quantitative approach was employed, utilizing a survey method with questionnaires distributed to auditors at the Financial and Development Supervisory Agency (BPKP) Representative Office of South Sulawesi Province. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), incorporating Measurement Invariance of Composite Models (MICOM) and Multi-Group Analysis (PLS-MGA) to assess the model's stability across groups and over time relative to the COVID-19 pandemic. The results revealed that deferred tax assets, deferred tax liabilities, and tax planning had no significant effect on earnings management practices. The multi-group analysis further demonstrated that the onset of the COVID-19 pandemic did not significantly moderate these relationships, indicating a high degree of structural stability in the model. These findings suggest that from an auditor's standpoint, tax-related indicators are not perceived as primary drivers of earnings management. This study highlights the importance of professional skepticism. It suggests that auditors may prioritize other risk factors over tax accounts when assessing potential financial reporting biases, regardless of external economic crises.